Characterization of a Lytic Bacteriophage vB_EfaS_PHB08 Harboring Endolysin Lys08 against Enterococcus faecalis Biofilms - Yang, Dan (Microorganisms, 2020)
Enterococcus faecalis is an opportunistic pathogen that causes illnesses ranging from urinary tract infections to sepsis in humans and animals. However, the overuse of antibiotics has increased rates of drug resistance among E. faecalis isolates. Bacteriophages and their derivatives have recently been identified as good candidates for the treatment of drug-resistant bacterial infections. Here, we isolated a virulent E. faecalis phage, PHB08, using the double-layer plate method. The bioactivity of the phage was determined via one-step growth curve testing and bacterial killing assays, and whole-genome sequencing was performed using the Illumina HiSeq platform. In addition, protein expression and antibiofilm assays were performed to investigate the activity of the phage lysin. Results showed that PHB08 has a 55,244-bp linear double-stranded DNA genome encoding 91 putative coding sequences. PHB08 inhibited the growth of host strain EF3964 at 37 °C in tryptic soy broth (TSB) medium, while in vegetable models, PHB08 caused a 4.69-log decrease in viable E. faecalis cells after 24 h. Both PHB08 and its endolysin lys08 showed antibiofilm activity against E. faecalis biofilms, which was enhanced by Mn(2+) ions. Thus, virulent phage PHB08 and endolysin lys08 may be good candidates for reducing and/or eradicating E. faecalis infections.